Inhaled iloprost for sarcoidosis associated pulmonary hypertension - Baughman, R.P.; Judson, M.A.; Lower, et al., E.E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Rationale: Patients with sarcoidosis associated pulmonary hypertension (SAPH) have responded to systemic prostacyclin therapy. Objectives: To determine the rate of response to inhaled prostacyclin, iloprost, in SAPH. Methods: Sarcoidosis patients with pulmonary hypertension and no evidence for left ventricular dysfunction were enrolled in an open label, prospective study. Patients underwent right heart catheterization and six minute walk (6MW) test. Quality of life was evaluated using several instruments, including the Saint George Respiratory Questionnaire (SGRQ). Patients received 5 mcg of inhaled iloprost every 2-3 hours while awake. After four months of therapy, patients underwent repeat cardiac catheterization, 6 MW test, and completed quality of life questionnaires. Measurements and Main Results: Of the 22 patients enrolled, 15 completed all 16 weeks of therapy. The most common reasons for study discontinuation included drug associated cough (3 patients) and compliance with the prescribed number of treatments per day (2 patients). Six patients experienced a 20% or greater decrease in pulmonary vascular resistance (PVR) from baseline with five of these six patients also showing 3 5 mm Hg reduction in PA mean. Although three patients improved the 6MW distance by at least 30 meters, only one had a decrease in PVR. At 16 weeks a significant decrease was reported in the SGRQ activity score (p=0.0273), with seven patients having a 4 point or greater decrease. Conclusion: Inhaled iloprost as monotherapy was associated with an improvement in pulmonary hemodynamics and quality of life as assessed by the SGRQ activity score in some sarcoidosis patients with SAPH.